The Influence of Mutual Fund and Fund ‎Management Characteristics on Financial Inefficiency: An Empirical Study of Equity ‎ Mutual Funds in Thailand - Supornrungcharoen , Janjao; Hensawang , Surang; Siriwattanakul , Dhanawat; Laohavichien, Tipparat; Kobkanjanapued, Yodsawinkan (International Journal of Accounting and Economics Studies, 2025)
Even though equity mutual funds offer an attractive investment alternative, the inefficient funds lead to suffering for all ‎stakeholders. Therefore, this research was conducted to investigate how mutual fund and management characteristics ‎influence on inefficiency of equity mutual funds in Thailand. The samples included 254 equity mutual funds, and the ‎study period was from 2019 to 2021. Data were analyzed through logistic regression (Logit). The results revealed that both ‎fund age and management tenure had a statistically significant negative influence on financial distress. The GDP growth ‎rate and interest rate had statistically significant negative and positive influences, respectively. This research contributes ‎to the literature by highlighting the counterintuitive role of fund age and manager tenure in driving mutual fund ‎inefficiency within the Thai capital market context‎.